Asparagus tamariscinus (Asparagaceae Juss.) – is a promising species for vertical greenery - Karakulov Anatoly (EDP Sciences, 2021)
Use of vertical greenery techniques for decorating hedges, walls of buildings and constructions, which allows to reduce the noise level, is hampered by an insufficient assortment of plants suitable for cultivation outdoors in Siberia and the Russian Far East. Asparagus tamariscinus, a high decorative, winter-hardy, and drought-resistant herbaceous polycarpicus, is a promising species that can fill this gap.